Pengaruh Program Pengembangan Kompetensi dan Insentif Kerja Terhadap Kinerja Karyawan Pelaksana di PT Perkebunan Nusantara IV Regional 4 - Uswatun Hasanah; Novi Peramasari; Nayla Desviona (Universitas 45 Surabaya, 2026)
The success of the palm oil and tea plantation industries is largely determined by the quality and motivation of Human Resources (HR) in the field. This study aims to analyze the effects of competency development programs and work incentives on the performance of operational employees at PT Perkebunan Nusantara IV Regional 4. The research employed a quantitative approach using a structured questionnaire distributed to 80 operational employee respondents through purposive sampling. Data analysis was conducted using SPSS software, including validity testing, reliability testing, classical assumption testing, and multiple linear regression analysis. The results showed that competency development (b₁ = 0.415, p < 0.05) and work incentives (b₂ = 0.485, p < 0.05) had a positive and significant effect on operational employee performance, both partially and simultaneously, with a contribution of 68.5% (R² = 0.685). These findings imply that improving the quality of competency development programs and implementing a fair incentive system are crucial strategies for the company to optimize operational productivity and reduce the percentage of harvest losses.